The isolation, preliminary characterization and biotransformation of a mutagen produced by Fusarium moniliforme Sheldon - Gelderblom, Wentzel Christoffel Andreas (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1982.